Hukum Alam dan Sunnatullah: Upaya Rekonstruksi Pemahaman Teologis di Indonesia - Eka Putra Wirman (ILMU USHULUDDIN, 2012)
This paper will provide a comprehensive understanding of the notion sunnatullāh and natural law, both in terms of science and the Qur’ān. Then it will also see the similarities and differences between the two. In this respect, the writer questions whether the sunnatullāh mentioned in the Qur’ān is similar to what meant by the laws of nature? Are the natural and all applicable laws inherently absolute and static?, and consequently they do not change gradually, and do not allow or support the development of science? Above questions need answers from the writers of theology, especially Indonesian, to discuss theology of nature in line with the discussion of nature itself which is done by scientists. So far there are indications these two terms have different purposes and meanings. This difference in the reformulation and reconstruction ultimately requires an understanding of theology, especially about the notion of natural law and sunnatullāh which has been the understanding of elementary students of theology and author in Indonesia.